THE USE OF MULTIMEDIA IN THE TEACHING OF FOLKLORE WORKS - Sabitova Tadzhikhan (Sciental Journals Publishing, 2025)
This article analyzes the theoretical and practical aspects of the effective use of multimedia in the process of teaching folklore works. In contrast to traditional educational styles, multimedia technologies – audio, video, animation, slides, through interactive programs-are based on the fact that folkloric patterns (fairy tales, epics, Proverbs, Legends) can be conveyed to students in a more lively, figurative and expressive way. The study highlights the role of these tools in increasing interest in readers in artistic-aesthetic worldview, national values and patterns of oral creativity. Conclusions have also been made that multimedia can help improve classroom effectiveness, enhance student activity, and develop independent thinking skills. The article is useful for teachers of folklore, educators specializing in language and literature, and specialists who aim to improve the modern course process.
Keywords: ICT, multimedia, video, audio, education, digital technology, text, graphics, folklore.